Phytochemical Screening and Emulgel Formulation of Jernang Resin Extract (Daemonorops Draco (Willd) Blume) - M, Wulandari; A, Arianto; Y, Yuandani (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: Daemonorops draco (Willd) Blume is a plant that produces jernang, which is a red resin that sticks to the outer skin of the fruit. Also known as dragon's blood, it is used as a traditional medicine for wound healing, anti-diarrhea, etc. as a natural coloring agent. Emulgel is an emulsion that contains a gel base in a certain ratio. Emulgel has the advantages of increasing drug absorption, easy to apply and more comfortable, not sticky on the skin. This study aims to determine the class of secondary metabolites contained in jernang in the form of simplicia and their extracts and to make jernang resin extract emulgel preparations that can be used as wound medicine. Method: Jernang simplicia collected by dry method. The extract was made by maceration using 96% ethanol solvent, separating the solvent using a rotary evaporator and concentrating it on a water bath. Phytochemical screening was carried out on simplicia and extracts. The emulsion formulation of jernang resin extract was made in three formulas with various levels of extracts P1 (2.5%), P2 (5%) and P3 (7.5%), using Tween 80 and Isopropyl myristate (IPA) as surfactants and oil phase, and 1% Carbopol as a gel base, then the emulgel was made with a ratio of emulsion and gel base of 4: 1 so that the variations of the extract were made into three formulas P4 (2%), P5 (4%) and P6 (6%) RESULTS: The results of phytochemical screening showed that jernang simplicia contained flavonoid, glycoside and saponin compounds. Also compounds that are non-polar, namely steroids / triterpenoids. Whereas in the form of the extract it contains flavonoid class compounds, this is because the 96% ethanol solvent is semi-polar so that the compounds contained in the ethanol extract are polar compounds, namely flavonoids which are the largest content of compounds in jernang. Jernang P4 extract emulgel (2%) organoleptically has the best physical appearance, has the characteristics of a thick, slightly clear consistency, brownish red color, has a distinctive smell of jernang mixed with the aroma of Tween 80, and is homogeneous. Conclusion: Based on the test results, it can be concluded that in the form of jernang simplicia, it contains polar compounds (flavonoids, glycosides and saponins) and non-polar (steroid / terponoid groups) and in the form of jernang resin extract contains flavonoid class compounds. Organoleptically, the jernang resin extract emulgel with a content of 2% (P4) is the best formula compared to other formulas.